Konsekuensi Yuridis Asas Konsensual Dalam Pasal 1320 Kuhperdata (Studi Pada Kasus Pembatalan PPJB) - Feby Amalia Hutabarat; Paramita Prananingtyas (Magister Kenotariatan Universitas Diponegoro, 2023)
Abstract The legal relationship of the sale and purchase agreement is dynamic. The legal issue that often arises in the agreement is state monodualism. First, the state is in a state of coercion. Second, abuse of circumstances. This article has the first objective: to examine the principle of consensuality in the cancellation of the sale and purchase agreement and to explain the juridical consequences or legal implications if the cancellation of the sale and purchase agreement contains monodualism. The research method used is the normative juridical method and the analysis orientation uses the case study. The case is elaborated using honesty theory and individualization theory. The results obtained are that in the a quo case, monodulism occurs, depending on the perspective of the parties. The buyer is pro against coercive circumstances, while the seller is pro against abusing circumstances. The principle of consensuality guides the parties to an agreement based on honesty, make sense and propriety. The legal implication is, firstly, the parties can be free from the binding agreement. The second situation is the misuse of the situation when viewed subjectively without looking at the objective, there will be legal uncertainty and a loss of sense of justice. Keywords: Consensuality Principle; Overmacht; Undue influence Abstrak Hubungan hukum perjanjian jual beli bersifat dinamis. Isu hukum yang sering muncul dalam perjanjian tersebut adalah monodualisme keadaan. Pertama, keadaan dalam kondisi memaksa. Kedua, penyalahgunaan keadaan. Artikel ini bertujuan pertama: mengkaji asas konsensualitas dalam pembatalan perjanjian pengikatan jual beli dan menjelaskan konsekuensi yuridis atau implikasi hukum jika pembatalan perjanjian pengikatan jual beli tersebut mengandung dua keadaan (monodualisme). Metode penelitian yang digunakan adalah metode yuridis normatif dan orientasi analisis menggunakan pendekatan kasus pembatalan perjanjian pengikatan jual beli. Kasus dielaborasi menggunakan teori kejujuran dan teori individualisasi. Hasil yang diperoleh bahwa dalam pembatalan perjanjian pengikatan jual beli kasus a quo, terjadi monodualisme keadaan, tergantung perspektif para pihak. Pihak pembeli pro terhadap keadaan memaksa sementara itu pihak penjual pro terhadap penyalahgunaan keadaan. Asas konsensualitas memandu para pihak bersepakat berlandaskan kejujuran dan sebab-sebab yang masuk akal (make sense) serta kepatutan. Implikasi hukumnya, pertama para pihak dapat terbebas dari perjanjian yang mengikatnya. Keadaan kedua, penyalahgunaan keadaan jika dilihat subyektif semata tanpa mencermati obyektifnya maka terjadi ketidakpastian hukum dan hilangnya rasa keadilan. Kata Kunci: Asas Konsensualitas; Keadaan Memaksa; Penyalahgunaan Keadaan